Influence of dietary conjugated linoleic acid (CLA) on lipid and fatty acid composition in liver and flesh of Atlantic salmon (Salmo salar) - Kennedy, Sean Robert; Campbell, Patrick; Porter, Allan R; Tocher, Douglas R (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2005)
The aim of the present study was to determine the effects of conjugated linoleic acid (CLA) on lipid and fatty acid metabolism in Atlantic salmon. The overall objective being to test the hypotheses that CLA has beneficial effects in salmon including growth enhancement, improved flesh quality through decreased adiposity and lipid deposition thereby minimising detrimental effects of feeding high fat diets, and increased nutritional quality through increased levels of beneficial fatty acids including n-3 highly unsaturated fatty acids (HUFA) and CLA itself. Salmon smolts were fed diets containing two levels of fish oil (low, ~18% and high, ~34%) containing three levels of CLA (a 1:1 mixture of 9-cis,trans-11 and trans-10,cis-12. at 0, 1 and 2% of diet) for 3 months and the effects on growth performance, liver and muscle (flesh) lipid contents and class compositions, and fatty acid compositions determined. The diets were also specifically formulated to investigate whether the effects of CLA, if any, were more dependent upon absolute content of CLA in the diet (as percentage of total diet) or the relative level of CLA to other fatty acids. Dietary CLA in salmon smolts had no effect on growth parameters or biometric parameters. However, there was a clear trend of increased total lipid and triacylglycerol contents in both liver and flesh in fish fed CLA, particularly in fish fed the high oil diets. Finally, CLA was incorporated into tissue lipids, with levels in flesh being 2-fold higher than in liver, but importantly, incorporation in liver was at the expense of saturated and monounsaturated fatty acids whereas in flesh it was at the expense of n-3HUFA.